Optimal Dose of Vitamin D For Covid-19 Treatment - Utami, Dita Mega; Ash-Siddiq, Muhammad Abdurrahman Rasyid; Rahmahani, Desi Rianti; Mubarok, Muhammad Iqbal, Muhammad Zulkifly Tasman; Sibarani, Jeremy Nicolas; Fauziyah, Habibah Teniya Ariq; Utomo, Budi; Fauziyah, Shifa (Folia Medica Indonesiana, 2022)
Highlights: • Vitamin D supplementations in different doses yield different outcomes. • Multi-day vitamin D administration of 1000-6000 IU in patients with COVID-19 has more positive impacts than a single high dose of vitamin D. • Patient morbidity, length of hospitalization, and patient mortality improved with multi-day vitamin D administration. Abstract: This meta-analysis aimed to determine whether there is any optimal dose of vitamin D for morbidity, length of hospitalization, and mortality in patients with COVID-19. We conducted a comprehensive search in three online databases for eligible studies until February 28, 2022. Odds ratio (OR) and standardized mean difference (SMD) were applied as summary statistics of primary outcomes. The study quality of the literatures collected was assesed using the Cochrane risk of bias tool version 2 (RoB 2). Eight randomized clinical trials (RCT) were included in the study. In our analysis, we found that there was no significant difference in morbidity when vitamin D was administered to COVID-19 patients [OR=0.50 (95% CI=0.13-1.96); SMD=-0.14 (95% CI=-0.55-0.28)]. Duration of hospitalization [SMD=-0.12 (95% CI=-0.39-0.15)] and mortality [OR 0.47 (95% CI=0.19-1.17)] of COVID-19 patients in five studies also showed no significant difference compared to patients who do not take vitamin D. However, when we analyzed two other studies, we found that in patients who did not take vitamin D, mortality was lower [SMD=0.43 (95% CI=0.29, 0.58)]. Compared to a single high dose of vitamin D, the multi-day vitamin D administration of 1000-6000 IU in patients with COVID-19 resulted in improved patient morbidity, length of hospitalization, and patient mortality.